Evaluation of Spatial Expansion of Rift Valley Lakes Using Satellite Data: A Brief Study - Rose Yang Mulama; Jephter Ongige Ondieki (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Assessing and studying lake expansion can reveal important information about climate change and regional responses; normally, a lake recedes during the dry season and floods during the wet season. In recent years, Lake Nakuru has had variations between dry and wet seasons’ water levels, suspected to be caused by increasing watershed land conversion to intensive crop production and urbanization, both reduce the capacity of soils to absorb water, recharge groundwater and thus increase seasonal flooding. The present work assessed the expansion and fluctuation of Lake Nakuru in Kenya by using satellite data and information. This study was carried out in the Lake Nakuru area in Nakuru County using two methods. In the first method, data was obtained from the USGS website, whereby Landsat 7 and 8 images were used, though images collected after May 31, 2003, had data gaps when the SLC failed, the images had about 78% of their pixels missing. In the second method shapefiles were used, to find out how the lake surface area had changed, it was done by using different methods. Surface water magnitude was measured from optical sensors, such as Landsat. ENVI software was used to process and analyze data from the satellite images. The data was then used to create a shapefile to get the area of the lake only. The shapefiles were classified using both Supervised and Unsupervised classification, and the area of the lake was obtained in hectares. The obtained area in hectares was recorded in a table and graphs were plotted to show the trend of the lake in the years 1972-2019. Furthermore, correlation was done by assuming the area of the shapefile before any classification is more accurate, therefore, it was compared with the other results obtained by using different methods. Maximum likelihood gave the best correlation values. For R2, it gave 0.8627, and R was 0.9312. The perfect correlation coefficient is 1, the graphs for correlation gave 0.91 for NDVI, 0.83 for K-MEANS, 0.93 for Maximum Likelihood and 0.92 for Spectral Angle Mapper. In conclusion, the change was seen using a line graph and that the Lake Nakuru area is expanding from the years 2010 to 2018.